A diallel analysis of a maize donor population response to in vivo maternal haploid induction: II. Haploid male fertility. Issue 2 (11th March 2020) - De La Fuente, Gerald N.; Frei, Ursula K.; Trampe, Benjamin; Ren, Jiaojiao; Bohn, Martin; Yana, Nicole; Verzegnazzi, Anderson; Murray, Seth C.; Lübberstedt, Thomas
Abstract: Doubled haploid (DH) lines are used in maize ( Zea mays L.) breeding to accelerate the breeding cycle and create homogenous inbred lines in as little as two seasons. These pure inbred lines allow breeders to quickly evaluate new cross combinations. There are two important steps in creating DH lines: (a) generation and selection of haploid progeny, and (b) genome doubling to create fertile, diploid inbreds. Colchicine is widely used to artificially double genomes in haploid plants, which is hazardous, expensive, and time consuming. In this study, three public inbred lines—A427, A637, and NK778—were found to have substantial haploid male fertility (HMF). A six‐parent full diallel between these three HMF lines and three non‐HMF lines was created and HMF was scored. Diallel analysis revealed significant general combining ability (GCA) estimates of up to 17% for HMF, as well as significant specific combining ability (SCA) effects of up to 25%. No significant reciprocal effects were found. Haploid male fertility is promising to be incorporated into elite maize breeding programs to potentially overcome the need of using colchicine treatments for genome doubling. Colchicine aided doubling success rates varying from almost 0 to 30%. Haploid male fertility has an advantage over artificial genome doubling, in terms of both increased success rates and decreased costs for DH line production.